function [ldens,Dldens,D2ldens] = lpdfgbeta(x,a,b,aa,bb) % Evaluates the logged BETA PDF at x. % % INPUTS % x [double] m*n matrix of locations, % a [double] m*n matrix of First BETA distribution parameters, % b [double] m*n matrix of Second BETA distribution parameters, % aa [double] m*n matrix of lower bounds for (generalized) distribution, % bb [double] m*n matrix of upper bounds for (generalized) distribution % % OUTPUTS % ldens [double] m*n matrix of logged (generalized) BETA densities. % Dldens [double] m*n matrix of first derivatives of logged (generalized) BETA densities. % D2ldens [double] m*n matrix of second derivatives of logged matrix of logged (generalized) BETA densities. % % SPECIAL REQUIREMENTS % none % Copyright © 2003-2021 Dynare Team % % This file is part of Dynare. % % Dynare is free software: you can redistribute it and/or modify % it under the terms of the GNU General Public License as published by % the Free Software Foundation, either version 3 of the License, or % (at your option) any later version. % % Dynare is distributed in the hope that it will be useful, % but WITHOUT ANY WARRANTY; without even the implied warranty of % MERCHANTABILITY or FITNESS FOR A PARTICULAR PURPOSE. See the % GNU General Public License for more details. % % You should have received a copy of the GNU General Public License % along with Dynare. If not, see . ldens = -Inf( size(x) ) ; idx = find( (x-aa)>0 & (x-bb)<0 ) ; if length(a)==1 ldens(idx) = -betaln(a,b) + (a-1)*log(x(idx)-aa) + (b-1)*log(bb-x(idx)) - (a+b-1)*log(bb-aa) ; else ldens(idx) = -betaln(a(idx),b(idx)) + (a(idx)-1).*log(x(idx)-aa(idx)) + (b(idx)-1).*log(bb(idx)-x(idx)) - (a(idx)+b(idx)-1).*log(bb(idx)-aa(idx)); end if nargout >1 Dldens = ldens ; if length(a)==1 Dldens(idx) = (a-1)./(x(idx)-aa) - (b-1)./(bb-x(idx)) ; else Dldens(idx) = (a(idx)-1)./(x(idx)-aa(idx)) - (b(idx)-1)./(bb(idx)-x(idx)); end end if nargout == 3 D2ldens = ldens ; if length(a)==1 D2ldens(idx) = -(a-1)./(x(idx)-aa).^2 - (b-1)./(bb-x(idx)).^2 ; else D2ldens(idx) = -(a(idx)-1)./(x(idx)-aa(idx)).^2 - (b(idx)-1)./(bb(idx)-x(idx)).^2; end end